Preventing Domestic Violence by Changing Australian Gender Relations: Issues and Considerations. Issue 2 (2nd April 2020) - Kuskoff, Ella; Parsell, Cameron
ABSTRACT: In recent years Australian governments have significantly refocused domestic violence policies to prioritise primary prevention strategies. The objective of such strategies is to change how Australians perceive, acknowledge, and respond to domestic violence as a gender-based problem. Recognising the value of these efforts to address oppressive cultural practices, we draw attention to limitations inherent in shifting culture as a means to prevent domestic violence. We demonstrate how governments may improve policy approaches by addressing the structural inequalities that have historically forced women into positions of subordination. This will help us move toward more effective and long-term solutions to domestic violence. IMPLICATIONS Australian domestic violence policy must include structural and systems changes prioritising women's equal rights in addition to equal opportunities. To change cultural attitudes and behaviours, we must alter the environment in which oppressions and opportunities are located. Social workers can shape the debate to ensure that changing culture to prevent domestic violence is conceptualised as part of a wider social and policy change agenda.